2016
DOI: 10.1063/1.4960181
|View full text |Cite
|
Sign up to set email alerts
|

Upgrade of Langmuir probe diagnostic in ITER-like tungsten mono-block divertor on experimental advanced superconducting tokamak

Abstract: In order to withstand rapid increase in particle and power impact onto the divertor and demonstrate the feasibility of the ITER design under long pulse operation, the upper divertor of the EAST tokamak has been upgraded to actively water-cooled, ITER-like tungsten mono-block structure since the 2014 campaign, which is the first attempt for ITER on the tokamak devices. Therefore, a new divertor Langmuir probe diagnostic system (DivLP) was designed and successfully upgraded on the tungsten divertor to obtain the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 30 publications
4
72
0
Order By: Relevance
“…The measurements of divertor LPs show that the power decay length exhibits q,div = 4.97I p −0.94 ( q,div = 1.46B p −1. 15 ), in good agreement with the particle decay length js = 4.74I p −1.02 ( js = 1.34B p −1.21 ). Similar trend measurements have also been demonstrated by the reciprocating LPs.…”
Section: Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…The measurements of divertor LPs show that the power decay length exhibits q,div = 4.97I p −0.94 ( q,div = 1.46B p −1. 15 ), in good agreement with the particle decay length js = 4.74I p −1.02 ( js = 1.34B p −1.21 ). Similar trend measurements have also been demonstrated by the reciprocating LPs.…”
Section: Introductionsupporting
confidence: 79%
“…It is demonstrated that both divertor particle and heat flux widths in EAST L-mode plasmas exhibit a strong negative dependence on I p (or B p ), i.e., js = I p −1.02 (or js = B p −1.21 ), q,div = 4.97I p −0.94 (or q,div = 1.46B p −1. 15 ), which provide more information on the prediction of particle and heat flux deposition width for ITER. Moreover, it is also demonstrated in EAST L-mode plasmas that the inverse I p (or B p ) scaling is independent of divertor configurations (LSN, DN and USN), which is good news for tokamaks operated in DN configurations, since the divertor heat flux widths do not narrow with respect to the SN case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent experiment of EAST, the divertor particle flux, which is directly associated with SOL parallel flow, can be readily determined from the ion saturation current measurements by the newly upgraded triple Langmuir probe with a high time resolution. 43 The ion saturation current represents the particle flux as C ¼ n t C s ¼ j s /e ¼ 6.24 Â 10 22 j s (A cm À2 ), where n t and C s are the electron density and ion sound speed at the target, respectively. Here, a calculation for the divertor particle flux is not available due to the damage of probe head in our experiment.…”
Section: -6mentioning
confidence: 99%
“…The plasma current is 0.4 MA and the line-averaged plasma density is 2 × 10 19 m −3 . The distribution of the probe ion saturation current density on the target [16] was also given for comparison with the W atom flux. The vertical coordinate indicates the poloidal distance from the upper edge of the outer target schematically shown on the right.…”
Section: In-situ Monitoring Of W Sputtering Sourcementioning
confidence: 99%